Generalised scaling law for soft contact tribology: Influence of load and asymmetric surface deformation. (November 2021) - Xu, Yuan; Cartwright, Ben; Advincula, Lian; Myant, Connor; Stokes, Jason R.
Abstract: Finite Element Analysis is used to investigate surface deformation associated with traction and normal forces within soft contact tribology (SCT). Significant deviation from the Hertzian contact model occurs, including asymmetric deformation in soft substrates. A cavity is predicted in front of the contact that has a characteristic length scale significantly larger than the film thickness expected in lubricated SCT. This cavity may facilitate fluid entrainment and squeeze out dynamics in boundary-mixed lubrication regimes that would explain many anomalous results in SCT studies. Analysis of contact mechanics reveals scaling parameters for the boundary-mixed and EHL regimes in SCT, which are used to generalise Stribeck friction curves onto a "single" curve as a function of a modified Hersey number at varying loads. Graphical Abstract: ga1 Highlights: Mechanical model in soft tribology predicts deviations from Hertz contact model. An asymmetric substrate deformation predicts a leading cavity before contact. A leading cavity may promote lubricant entrainment within the boundary-mixed regime. New scaling laws are recommended for Stribeck analysis in soft contact tribology.